A Study on Students’ Adversity Quotient and Academic Performance in English Subject - Kuhon, Fiola (Study Program of English Literature, 2020)
ABSTRACT The aim of this study is to observe students’ Adversity Quotient and their Academic Performance, in this case English subject. From many previous studies, there is a high indication that Adversity Quotient plays an important role in students’ academic performance. Therefore, this study was carried out to observe that hypothesis. Quantitative method was used wherefore the data was in form of numbers, namely from Adversity Quotient test and students’ final grade in English class. The findings showed that majority of the students who exceled in academic performance were the students whose test results showed that they were classified with high level of Adversity Quotient. Furthermore, as this study included 2 groups of students, the data depicted that the adult students performed a better result in AQ test than the fresh graduate students who were both in the same semester. Keywords: ABSTRACT The aim of this study is to observe students’ Adversity Quotient and their Academic Performance, in this case English subject. From many previous studies, there is a high indication that Adversity Quotient plays an important role in students’ academic performance. Therefore, this study was carried out to observe that hypothesis. Quantitative method was used wherefore the data was in form of numbers, namely from Adversity Quotient test and students’ final grade in English class. The findings showed that majority of the students who exceled in academic performance were the students whose test results showed that they were classified with high level of Adversity Quotient. Furthermore, as this study included 2 groups of students, the data depicted that the adult students performed a better result in AQ test than the fresh graduate students who were both in the same semester. Keywords: Adversity Quotient, Academic Performance, Students